2016
DOI: 10.1177/0022219415620899
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of Arithmetic and Reading Disorder

Abstract: The aim of the present study was to investigate the cognitive profiles of primary school children (age 82-133 months) on a battery of basic number processing and calculation tasks. The sample consisted of four groups matched for age and IQ: arithmetic disorder only (AD; n = 20), reading disorder only (RD; n = 40), a comorbid group ( n = 27), and an unimpaired control group ( n = 40). Multiple 2 (RD vs. No RD) × 2 (AD vs. No AD) factorial ANCOVAs showed that children with RD had selective impairments in countin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 53 publications
(95 reference statements)
0
30
1
3
Order By: Relevance
“…The lower reading fluency among dyscalculia group should be noted. However, Raddatz et al ( 2016 ) showed that a lower reading fluency does not influence accuracy and RTs in our task selection.…”
Section: Methodscontrasting
confidence: 52%
“…The lower reading fluency among dyscalculia group should be noted. However, Raddatz et al ( 2016 ) showed that a lower reading fluency does not influence accuracy and RTs in our task selection.…”
Section: Methodscontrasting
confidence: 52%
“…However, phonological awareness was also predictive of mathematical performance, suggesting that a shared deficit in phonological processing may underlie both RD and MD. Similarly, Raddatz et al (93) found that MD children showed deficits in various non-verbal and verbal tasks related to number processing, whereas RD children showed deficits in verbal tasks.…”
Section: An Overview Of Cognitive Profiles Of Comorbid Math and Readimentioning
confidence: 88%
“…Similarly, previous research has shown neither explanation can account for homotypic comorbidity (i.e. reading disorder and mathematics disorder) (Moll, Göbel, & Snowling, 2015;Raddatz, Kuhn, Holling, Moll, & Dobel, 2016).…”
mentioning
confidence: 79%